The pharmacist’s role in the periprocedural management of anticoagulation in Canada: A qualitative study protocol - Chioma S. Okpalaora; Stephanie W. Young; Tiffany A. Lee (PLoS ONE, 2026)
Anticoagulants are crucial for both the immediate and ongoing management of thromboembolic disorders, including atrial fibrillation and venous thromboembolism, and for patients with mechanical heart valves. However, their management during the periprocedural period requires carefully balancing thromboembolic and bleeding risks, underscoring the need for coordinated and structured periprocedural anticoagulation management (PAM). Pharmacists, with their comprehensive training and expertise in medication management, are well positioned to deliver PAM. However, empirical evidence related to the roles of Canadian pharmacists in PAM, or the barriers, facilitators, and organizational structures that shape their practice is lacking. This protocol paper outlines a qualitative study that uses a qualitative description design grounded in constructionism and naturalism. The study aims to provide an in-depth understanding of pharmacists’ roles and experiences in PAM across Canada, while exploring variations by demographic and practice characteristics. Using purposeful maximum variation sampling, licensed Canadian pharmacists with at least 6 months of current PAM experience will be recruited to take part in one semi-structured interview conducted virtually using Microsoft Teams. Interviews will be recorded and transcribed verbatim and analyzed using conventional qualitative content analysis to inductively generate codes and categories. The findings of this research will address gaps in the literature by providing a detailed description of pharmacists’ roles in PAM and the contextual factors influencing practice across diverse regions and settings in Canada. Findings may inform future PAM service models, professional training, and health system policies to support optimal care coordination and improved patient outcomes in the Canadian anticoagulation care landscape.